Impedance cardiography: a comparison of cardiac output vs waveform analysis for assessing left ventricular systolic dysfunction. - DeMarzo AP; Kelly RF; Calvin JE (Progress in Cardiovascular Nursing)
Early detection of asymptomatic left ventricular systolic dysfunction (LVSD) is beneficial in managing heart failure. Recent studies have cast doubt on the usefulness of cardiac output as an indicator of LVSD. In impedance cardiography (ICG), the dZ/dt waveform has a systolic wave called the E wave. This study looked at measurements of the amplitude and area of the E wave compared with ICG-derived cardiac output, stroke volume, cardiac index, and stroke index as methods of assessing LVSD. ICG data were obtained from patients (n=26) admitted to a coronary care unit. Clinical LVSD severity was stratified into 4 groups (none, mild, moderate, and severe) based on echocardiography data and standard clinical assessment by a cardiologist blinded to ICG data. Statistical analysis showed that the E wave amplitude and area were better indicators of the level of LVSD than cardiac output, stroke volume, cardiac index, or stroke index. ICG waveform analysis has potential as a simple point-of-care test for detecting LVSD in asymptomatic patients at high risk for developing heart failure and for monitoring LVSD in patients being treated for heart failure. (Prog Cardiovasc Nurs. 2007;22:145-151).